High frequency vortex dynamics in YBa2Cu3O7−x with Ba2YTaO6-Ba2YNbO6 nanodefects. (June 2020) - Torokhtii, K.; Alimenti, A.; Rizzo, F.; Augieri, A.; Celentano, G.; Frolova, A.; Silva, E.; Pompeo, N.
Abstract: We studied pinning characteristics of YBa2 Cu3 O7− x (YBCO) with 5 mol.% Ba2 YTaO6 /Ba2 YNbO6 (BYNTO). In contrast to widely used d.c methods, at microwaves very short oscillations of the fluxons are involved giving the information on both the pinning strength, through the pinning constant and on dissipation, related to the vortex core physics, through the viscosity η . We estimate the pinning constant kp, the vortex viscosity η and also the maximum creep factor χmax . The results were compared not only with the pristine YBCO sample but also with the effect of another type of columnar defects (BZO) in YBCO. All film samples were grown by Pulsed Laser Deposition (PLD) technique at nearly the same conditions to ensure the uniform. We detect an improvement of all pinning characteristics of YBCO-BYNTO sample in the temperature range 62 - 90 K and for field up to 0.75 T. While the average diameter of the defects is similar for YBCO-BYNTO and YBCO-BZO the key of the superior characteristics in YBCO-BYNTO could be both the concentration of columns and an addition of another phase of point-like defects.